Former Yugoslav Republic of Macedonia : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This 2016 Article IV Consultation highlights that the economy of the Former Yugoslav Republic of Macedonia has been growing at a solid pace on the back of strong domestic demand and exports. The real GDP is now 16 percent above its precrisis level. In 2015, GDP growth increased to 3.8 percent from 3.6 percent in 2014. The unemployment rate continues to decline. Headline inflation has hovered at zero for the last two years, while core inflation turned positive at the end of 2015. GDP growth is projected to soften in 2016 but pick up in the medium term contingent on the return of political stability.